2009
DOI: 10.3923/pjbs.2009.765.771
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Garlic Extract Against Acetaminophen-Induced Oxidative Stress and Glutathione Depletion

Abstract: Acetaminophen, the most commonly sold over-the-counter antipyretic analgesic, is capable of causing severe and sometimes fatal hepatic damage in humans and experimental animals. The incidence of liver injury due to acetaminophen overdose, either with suicidal intent or by accident, is increasing. Garlic is among those medicinal plants famous for its different health protective effects. In this study, the protective effects of garlic extract on acute acetaminophen-induced liver injury were investigated using fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…APAP-induced cytotoxic effects that relate to an increase in the generation of reactive oxygen species (ROS) were previously reported (65,66). However, it is still unclear which ROS elements are increased upon APAP treatment.…”
Section: Resultsmentioning
confidence: 90%
“…APAP-induced cytotoxic effects that relate to an increase in the generation of reactive oxygen species (ROS) were previously reported (65,66). However, it is still unclear which ROS elements are increased upon APAP treatment.…”
Section: Resultsmentioning
confidence: 90%
“…In order to measure glutathione levels, hepatocytes were isolated from male Sprague-Dawley rats and incubated with different concentrations of garlic extract at three different times: before, at the same time and 30 min after addition of acetaminophen. The results were collected at different time points (from 0 to 150 min) and it was observed that the intake of garlic extract is able to protect hepatocytes against acetaminophen-induced toxicity by increasing intracellular GSH levels (Anoush et al, 2009). …”
Section: Phase 2 Metabolism and Potential Pharmacokinetic Herb-drug Imentioning
confidence: 99%
“…Reduced glutathione can act as a reductant, reducing hydrogen peroxide and lipid hydroperoxides directly to H 2 O, a reaction catalyzed by GSH-Px [43]. Depletion of intracellular GSH, under conditions of continuous intracellular oxidative stress, leads to oxidation and damage of lipids, proteins, and DNA by the reactive oxygen species [44, 45].…”
Section: Paracetamolmentioning
confidence: 99%